Peran Quadruple Helix Dalam Pengembangan Pariwisata Halal di Kawasan Wisata Cisarua-Lembang - Rezqy, Vira Oktaviani; Fikriyah, Khusnul (Jurnal Ekonomika dan Bisnis Islam, 2021)
The development of halal tourism using the Quadruple Helix concept is a concept that combines the roles of four actors in supporting the halal tourism development program. This concept divides the roles of the Government, Academics, Private sector and Community to become a good collaboration in the development of halal tourism in the Cisarua-Lembang Tourism Area. This study aims to determine the role of Quadruple Helix actors in the development of halal tourism in the Cisarua-Lembang Tourism Area. In this study using a qualitative descriptive research method using primary data and secondary data. Interviews, field observations, and documentation are data collection techniques used in this study. The results of this study indicate that the role of the Quadruple Helix in the development of halal tourism in the Cisarua-Lembang Tourism Area has not played an optimal role and there has not been significant cooperation among Quadruple Helix actors.